Linking vocational archive data using an occupations and educations centric ontology - Reiser, Thomas [Verfasser]; Dörpinghaus, Jens [Verfasser]; Steiner, Petra [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2025)
"In this paper, an approach is presented for semantically enriching and linking historical vocational education and training (VET) documents using an ontology-centric method grounded in occupations and educational programs. The present study draws on a digitized corpus of archival documents from various political regimes in Germany — including the German Empire, the German Democratic Republic (GDR), and the Federal Republic Germany (FRG) — in order to explore strategies for annotating job titles and aligning them with standardized taxonomies such as KldB and ISCO. The proposed methodology integrates phrase matching, classification models, and ontology-based linking via the German Labor Market Ontology (GLMO), thereby enabling cross-referencing of documents by occupation and educational structure. The proposed workflow is designed to support longitudinal studies and promote interoperability across fragmented archival collections. This offers a scalable solution for labor market and education research." (Authors' abstract, BIBB-Doku)
Keywords: S 6 Berufsbereiche; T 1.2 Historische Berufsbildungsforschung; 370; 300; Berufsforschung; Historische Berufsbildungsforschung; Berufsklassifikation; Textanalyse; Texterkennung